2016
DOI: 10.1681/asn.2016010069
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants Associated with Circulating Parathyroid Hormone

Abstract: Parathyroid hormone (PTH) is a primary calcium regulatory hormone. Elevated serum PTH concentrations in primary and secondary hyperparathyroidism have been associated with bone disease, hypertension, and in some studies, cardiovascular mortality. Genetic causes of variation in circulating PTH concentrations are incompletely understood. We performed a genome-wide association study of serum PTH concentrations among 29,155 participants of European ancestry from 13 cohort studies (n=22,653 and n=6502 in discovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 84 publications
4
63
0
Order By: Relevance
“…We determined the effects of identified human genetic variants within the PDZ motif of RGS14 on NHERF1 binding, and found that one (Asp 563 Asn) disrupted the RGS14:NHERF1 complex and blocked RGS14 actions. RGS14 is implicated by numerous GWAS studies to be involved in various forms of chronic kidney diseases (14)(15)(16)(17)(18)(19). Relevant to that, we identified here at least one human genetic variant that blocks RGS14 actions on PTH-sensitive phosphate uptake.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…We determined the effects of identified human genetic variants within the PDZ motif of RGS14 on NHERF1 binding, and found that one (Asp 563 Asn) disrupted the RGS14:NHERF1 complex and blocked RGS14 actions. RGS14 is implicated by numerous GWAS studies to be involved in various forms of chronic kidney diseases (14)(15)(16)(17)(18)(19). Relevant to that, we identified here at least one human genetic variant that blocks RGS14 actions on PTH-sensitive phosphate uptake.…”
Section: Discussionsupporting
confidence: 56%
“…The RGS14 PDZ ligand is present throughout the primate order and in sheep. RGS14 has been implicated by numerous GWAS studies in various forms of chronic human kidney diseases (14)(15)(16)(17)(18)(19). Relevant to that, we identify here one human genetic variant (D563N) that disrupts RGS14 binding to NHERF1 and its capacity to inhibit PTH-sensitive phosphate uptake.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…GWAS concerning serum PTH concentrations in European ancestry showed that among genes showing the most influential association with serum PTH levels are rs6127099 upstream of CYP24A1 that encodes the catabolic enzyme for 1, 25-dihydroxyvitamin D and 25-dihydroxyvitamin D, and rs73186030 near CASR [16]. Other CASR SNPs, rs7652589 [6] and rs1801725 [7], were individually involved in serum PTH levels in HD patients.…”
Section: Introductionmentioning
confidence: 99%